PREVALENCE OF SOME IDENTIFIED PROSTATE PROBLEMS AMONG PEOPLE RESIDENT IN IMO STATE, NIGERIA. - A. U., Opara,; G. C., Uloneme,; P., Nwankpa,; D., Akukwu,; J., Ekezie (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Adult males aged forty years and above resident in Imo State (both indigenesand non indigenes) who visited the state owned health institutions in the stateand also the Federal Medical Centre Owerri constituted the population of thestudy. A sample size of one thousand and ten (1010) patients’ caserecords/reports were on request, made available, randomly from theinstitutions’ records departments for a survey. A careful investigation of thecase records showed that as many as three hundred and twenty six (326) of thepatients (representing 32.3%) were diagnosed, managed or treated of prostaterelated problems, identified as benign prostatic hyperplasia (BPH), prostatitisor cancer of the prostate. The prevalence of these prostate problems was alsoseen to increase with age, as observed in people above seventy years of agewhere over 48% of them was diagnosed of one form of prostate problem or theother. Sadly, again, the results of the study showed that the prevalence ofprostate problems among adult males resident in Imo State increased as theyears passed by.